Best Interest Principle’ for the Education of a Child - Hariharan, Prabha (JOURNAL OF INDIAN EDUCATION, 2013)
Our education system is going through a very important phase where its inadequacies are being revealed by various national and international educational outcome comparisons. While many states are taking up innovative educational experiments and practices, the overall picture of our educational outcomes still needs improvement. In this scenario, we need to clarify the guiding principles for the processes and practices of our education system with focus on the main goal of successful educational outcomes for all children. This article presents a framework called the ‘Best Interest Principle’ for the education of a child. This framework brings together three major factors that can be thought of as providing guidance to the processes and practices in our educational system.